Postwar Soviet Politics : the Fall of Zhdanov and the Defeat of Moderation, 1946-53 - Hahn, Werner G. (Cornell University Press, 2019)
In the years immediately following World War II, the Soviet Union witnessed a revival of tight Stalinist controls. Werner G. Hahn here explores the politics behind the USSR's rejection of moderation and seeming willingness to collaborate with the West, in favor of cold-war militancy abroad and inflexible dogmatism at home. Basing his work on scrupulous research in Soviet newspapers, journals, and books of the period, Hahn asserts that contrary to accepted opinion, there was vigorous debate between the Soviet conservatives and moderates in the early postwar period. In addition to documenting the events of the late 1940s and early 1950s, Hahn discusses the impact of the moderates' defeat in 1948-49 not only on contemporary Soviet politics, but also on Soviet science, philosophy, and economic thought. Illuminating an era of crucial importance in Soviet history-the final years of Stalin's reign.-this book will interest historians, political scientists, and students of contemporary Soviet affairs.